MASA KERJA CEO DAN MANAJEMEN LABA (CEO TENURE AND EARNIGS MANAGEMENT) - Vernando, Andreas; Rakhman, Fuad (UI Scholars Hub, 2018)
This study aims to investigate the CEO behavior in managing earnings during his tenure. This study predicts that the CEO will overstate earnings in the early years and the final year of his service. Prior studies investigating earnings management only focused on either the early years or the final year of CEO service without considering CEO tenure between the early years and the final year of CEO service. Study investigating earnings management during CEO tenure was still scarce (Ali and Zhang 2015). Further, prior studies predicted that new CEO would engage in income-decreasing earnings management that was explained by big bath theory. However, this study predicts that CEO in early years of their services will engage in income-increasing earnings management that can be explained by career concern theory. Therefore, this study contributes to fill the gap in the literature. Using the sample of nonfinancial companies listed in the Indonesia Stock Exchange from 2005 to 2014, this study finds that CEO will overstate earnings in the early years of his services. However, this study does not find that CEO overstate earnings in the final year of his services.